CRONE control based anti-icing/deicing system for wind turbine blades. (November 2016) - Sabatier, J.; Lanusse, P.; Feytout, B.; Gracia, S.
Abstract: This paper presents an application of CRONE control, a robust control based on fractional order differentiation, to an anti-icing/deicing system for wind turbine blades. The deicing system uses an electrically conductive polymer paint applied on the blade at ice formation areas. The voltage applied to the paint leads to its heating. Based on a temperature measure provided by various sensors placed on the blade, a control system can thus be used to prevent the blade icing up during wind turbine operation or to deice the blade after a rest time. To design the control system, a thermal model of the blade with the paint was developed and its associated parameters were identified using tests in a climatic wind tunnel. A CRONE controller was then designed and its performance evaluated both on blade subparts in the climatic wind tunnel and on a floor-standing real blade.